Prosopis laevigata and Mimosa biuncifera (Leguminosae), jointly influence plant diversity and soil fertility of a Mexican semiarid ecosystem. - García-Sánchez, Rosalva (2012)
Prosopis laevigata and Mimosa biuncifera are frequently found in arid and semiarid shrublands, but scarce information is available about their influence on plant community structure and soil fertility. We compared plant community structure, diversity and soil nutrients of three semiarid shrubland sites located in Mezquital Valley, Mexico. These sites differ in their dominant species: Site 1 (Bingu) P. laevigata, Site 2 (González) M. biuncifera, and Site 3 (Rincón) with the presence of both legumes. The results showed that the plant community with P. laevigata and M. biuncifera (Site 3) had more cover, taller plants and higher plant diversity than sites with only one legume (Site 1 and Site 2). Soil organic matter (SOM), soil organic carbon (SOC), total nitrogen (TN), phosphorus-Olsen (P) and C mineralization were higher in the soil under the canopy of both legumes than in bare soil. In contrast, soil cation concentrations were lower under the canopy of P. laevigata, but not for M. biuncifera. In addition, the density of arbuscular mycorrhizal fungi spores was higher within the soil under the canopy of M. biuncifera than in the soil under the canopy of P. laevigata. Thus, resource islands (RI) created by P. laevigata increased the amounts of SOC, TN and P when compared with the RI of M. biuncifera. This study provided evidences about the importance of species identity in order to expand the niche availability for the establishment of other plants, and highlights that P. laevigata and M. biuncifera jointly influencing plant colonization within semiarid ecosystems.